Picture perfect? Gazing into girls' health, physical activity, and nutrition through photovoice. Issue 1 (1st January 2021) - Spencer, Rebecca A.; Numer, Matthew; Rehman, Laurene; Kirk, Sara F.L.
ABSTRACT: Background: Women face contradictions regarding their health: Pressure to be feminine, but also athletic; Criticism for being too sporty or muscular, but equally so for being perceived as lazy or overweight. These complexities are perpetuated through media and discourse. Purpose: Using a feminist post-structural approach and photovoice, this study explored health, physical activity, and nutrition in adolescent girls and young women. Methods: Photovoice enables reflection, promotes dialogue, and sparks change. The process involved conducting a workshop, collecting photos, and participatory analysis sessions, which engaged the participants (n = 7, ages 13–26) in photo selection, contextualization, and codifying. Results: This resulted in three themes: First, (Breaking) Stereotypes, in which participants identified gender norms, conflicts, and contradictions; Second, Emotional Safety, or the contexts in which girls and young women feel confident and comfortable; Finally, Being Outside in Nature emerged as significant. Each theme is supported by quotations and photographs. This work suggests being outside in nature provides important context for girls and young women to feel emotionally safe, such that they may engage in the complex navigation of competing discourses surrounding health.